supply chain performance analysis of milkfish using data envelopment analysis method (case study ud. tbs) - Windi Habsari; Mohammad Fuad Fauzul mu’tamar; Abdul Azis Jakfar (Universitas Muhammadiyah Sidoarjo, 2020)
An industry's supply chain system must be intensely improved to improve the company's performance. Factors that influence a performance are reliability, responsiveness, agility or flexibility, cost and assets. The performance of milk fish supply chain at UD TBS has not yet been measured by the performance of each distributor, so it is not yet known how effective the performance of the supply chain and the factors that can affect its performance. The purpose of this study was to determine the factors that influence the performance of milk fish supply chains and DMU values by the DEA method. The results showed that the most influential factor was cash-to-cash cycle time (the time needed by the distributor to the company in ordering milkfish. The effectiveness value of 20 distributors was obtained 85% effective (green) and 10% ineffective (amber) and 5% ineffective (red).